A model study of ground level ozone pollution in the High Tatras Mountain region - BIČÁROVÁ, Svetlana; FLEISCHER, Peter (Contributions to Geophysics and Geodesy, 2021)
Air pollution, especially ground level ozone (O3), negatively influences sensitive ecosystems of the Tatra National Park (UNESCO Biosphere reserve). The aim of this work is to analyse the role of long-range transport in extremely high ozone air pollution situation over the High Tatras Mountain region. Summer O3 episode observed during 12–14 August 2003 was modelled by coupled meteorological and photochemical mesoscale model MetPhoMod (Perego, 1999). Standard meteorological data and O3 concentration measured at fixed ground stations: Poprad – Gánovce, Stará Lesná, T. Lomnica – Štart, Skalnaté Pleso and Lomnický štít in vertical profile from 706 to 2634 m a.s.l. were used. Emissions and land cover type of model domain (20 × 18 km) were obtained from EMEP database and regional land use maps, respectively. Observed maximal O3 concentrations were about 60–90% higher than the simulated values (considered as local O3 forming potential). During the peak phase of investigated O3 episode, the contribution of local independent emission sources to observed O3 concentration was on average 37%. Achieved results indicate that long-range transport (from Western Europe) and descent of O3 enriched air from high troposphere to ground level supported by high pressure system played more significant role in O3 concentration increase than its local formation during the extremely high O3 events in the High Tatras Mountain region.